The Presence of Protozoan Parasites in Drinking Waters and Environmental Waters in Denizli City Center - Tuğba Sağlam; Serdar Düşen; Ülkü Karaman; Ergun Mete (Türkiye Parazitoloji Dergisi, 2022)

(untitled)
Objective:The presence of protozoan parasites in agricultural irrigation and drinking water resources at Denizli city center was investigated in detail for the first time.Methods:The research was carried out between October 2017 and October 2018 and 84 water samples were taken from 7 different stations identified from the Denizli city center. After examining the samples by direct visualization (Native-Lugol), they were stained with quinton’s acid fast, giemsa and trichrome dyes. The preparations were evaluated parasitologically under a light microscope.Results:Cryptosporidium spp. was detected in 21 (25%) of 36 agricultural irrigation water samples collected during the study, Cyclospora cayetanensis in 5 samples (5.95%) and Giardia spp. in 12 samples (14.28%). No parasite findings were found in any of the 48 drinking water samples collected.Conclusion:The widespread use of animal husbandry and agriculture as grazing land in the sampling stations, the mixing of domestic wastewater into these waters without any treatment, and seasonal conditions cause the protozoan parasites to be seen more in certain periods. It is thought that waterborne protozoan infections that may occur in the future can be significantly prevented by taking the necessary precautions in terms of public health and environmental animal husbandry.